Sequestration within biomolecular condensates inhibits Aβ-42 amyloid formation. Issue 12 (18th February 2021) - Küffner, Andreas M.; Linsenmeier, Miriam; Grigolato, Fulvio; Prodan, Marc; Zuccarini, Remo; Capasso Palmiero, Umberto; Faltova, Lenka; Arosio, Paolo
Abstract : Biomolecular condensates sequester an aggregation-prone peptide and prevent its aggregation, showing that heterotypic interactions within the condensates can prevent the formation of amyloid fibrils, despite the local increase in concentration. Abstract : Biomolecular condensates are emerging as an efficient strategy developed by cells to control biochemical reactions in space and time by locally modifying composition and environment. Yet, local increase in protein concentration within these compartments could promote aberrant aggregation events, including the nucleation and growth of amyloid fibrils. Understanding protein stability within the crowded and heterogeneous environment of biological condensates is therefore crucial, not only when the aggregation-prone protein is the scaffold element of the condensates but also when proteins are recruited as client molecules within the compartments. Here, we investigate the partitioning and aggregation kinetics of the amyloidogenic peptide Abeta42 (Aβ-42), the peptide strongly associated with Alzheimer's disease, recruited into condensates based on low complexity domains (LCDs) derived from the DEAD-box proteins Laf1, Dbp1 and Ddx4, which are associated with biological membraneless organelles. We show that interactions between Aβ-42 and the scaffold proteins promote sequestration and local increase of the peptide concentration within the condensates. Yet, heterotypic interactions within the condensates inhibit the formation of amyloid fibrils. These results demonstrate that biomolecular condensates could sequester aggregation-prone proteins and prevent aberrant aggregation events, despite the local increase in their concentration. Biomolecular condensates could therefore work not only as hot-spots of protein aggregation but also as protective reservoirs, since the heterogenous composition of the condensates could prevent the formation of ordered fibrillar aggregates.